“I am willing to do both well”: Chinese academic mothers facing tension in family and career - Bao, Li; Wang, Guanghua (Frontiers in Psychology, 2022)
Academic mothers perform intersected roles. They show their profession in workplaces, while they take the “second shift” of motherhood back to families. The contested expectations in family and career built by the heterosexual matrix give academic mothers tension. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by a Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that, in the masculine academia, these women academics helped maintain the heterosexual matrix by satisfying the gender normativity when they negotiated their performances in family and career; meanwhile, most have developed some strategies to achieve their career advancement.